Size-dependent interaction of the poly(N-vinyl-2-pyrrolidone) capping ligand with Pd nanocrystals - Xian, Junyang (Langmuir : the ACS journal of surfaces and colloids, 2012)
Pd nanocrystals were prepared by the reduction of a H(2)PdCl(4) aqueous solution with C(2)H(4) in the presence of different amounts of poly(N-vinyl-2-pyrrolidone) (PVP). Their average size decreases monotonically as the PVP monomer/Pd molar ratio increases up to 1.0 and then does not vary much at higher PVP monomer/Pd molar ratios. Infrared spectroscopy and X-ray photoelectron spectroscopy results reveal the interesting size-dependent interaction of PVP molecules with Pd nanocrystals. For fine Pd nanocrystals capped with a large number of PVP molecules, each PVP molecule chemisorbs with its oxygen atom in the ring; for large Pd nanocrystals capped by a small number of PVP molecules, each PVP molecule chemisorbs with both the oxygen atom and nitrogen atom in the ring, which obviously affects the structure of chemisorbed PVP molecules and even results in the breaking of involved C-N bonds of some chemisorbed PVP molecules. Charge transfer always occurs from a chemisorbed PVP ligand to Pd nanocrystals. These results provide novel insights into the PVP-metal nanocrystal interaction, which are of great importance in the fundamental understanding of surface-mediated properties of PVP-capped metal nanocrystals